Electroconvulsive seizures regulate various stages of hippocampal cell genesis and mBDNF at different times after treatment in adolescent and adult rats of both sexes - Ledesma-Corvi, Sandra; García-Fuster, M. Julia (Frontiers in Molecular Neuroscience, 2023)
Electroconvulsive therapy, a fast-acting option for treatment-resistant depression, is modeled at the preclinical level through the induction of electroconvulsive seizures (ECS) in rodents. Recent studies from our group proved sex-and age-differences in the antidepressant-like response elicited by ECS in rats; while an antidepressant-like response was observed in male adolescent and adult rats (although with greater efficacy in adulthood), the same parameters rendered inefficacious in females of any age. To better understand the potential sex differences taking place at the molecular level that might be mediating these behavioral disparities, we evaluated the impact of a repeated treatment with ECS (95 mA for 0.6 s, 100 Hz, 0.6 ms) in adolescent and adult rats of both sexes. Several hippocampal markers of neuroplasticity, commonly regulated by most antidepressants, such as those of neurogenesis (cell proliferation, neurogenic differentiation, long-term cell survival) or mBDNF and associated signaling (e.g., mTOR and ERK1/2) were evaluated at different time-points after treatment (1-, 8-, 15-and up to 30-days post-treatment). The main results demonstrated that ECS improved the survival rate of new cells born in the dentate gryus before treatment. Moreover, ECS increased cell proliferation and neurogenic differentiation at different times post-treatment, paired with persistent increases in mBDNF, observed long after treatment. In general, effects were different for each sex and varied with the age of the animal (adolescent vs adulthood). The present study is the first-one to demonstrate that such persistent molecular changes induced by ECS in hippocampus, some of them observed up to 30-days post-treatment, also occurred in female rats and adolescence. Although these molecular changes could not justify the lack of ECS efficacy described by these same parameters of ECS in female rats (vs. male rats), they proposed certain beneficial effects common to both sexes, and age periods studied, opening the avenue for further studies. Based on these neurochemical effects, ECS should have displayed similar efficacies for both biological sexes. Therefore, the reason behind these disparities should be further explored to better translate efficacious treatments specific and/or personalized for each sex to the clinic.